Do competition, regulation and stability matter for efficiency in Sub-Saharan African banking sectors? - Joseph Olorunfemi Akande (Cogent Economics & Finance, 2018)
The excessive cost of financial intermediation in the Sub-Saharan African banking sectors motivates the investigation of whether competition, regulation and stability matter for efficiency in the banking system. Data from 440 commercial banks for the periods 2006-2015 were collected and analysed by seven-variable panel structural vector autoregressive model. There was evidence to show that efficiency responds positively and significantly to shocks in capital, liquidity and asset quality regulations and competition. However, the results reveal all the variables responding to one standard deviation shock in efficiency, suggesting that while the variables matter for efficiency, they all also require efficiency for their effective operation. Hence, the conclusion is that efficiency is central to the effective running of the banking system.
Keywords: 330; efficiency; competition; regulation; stability; panel structural vector autoregressive model; commercial banks